Assessment and Spatial Distribution of Urban Ecosystem Functions Applied in Two Czech Cities - Renata Včeláková; Marcela Prokopová; Vilém Pechanec; Lenka Štěrbová; Ondřej Cudlín; Ahmed Mohammed Ahmed Alhuseen; Jan Purkyt; Pavel Cudlín (Applied Sciences, 2023)
As urban areas expand worldwide, the importance of ecosystem services provided by urban and peri-urban areas (ESs) increases, especially those that mitigate the effects of ongoing climate change. We present a relatively simple method to assess the performance of three ecosystem functions (EFs: evapotranspiration, carbon production, and habitat- and landscape-level biodiversity) in urban and peri-urban areas, indicating their capacity to provide relevant regulative ESs. The method was applied to two Czech foothill cities, Liberec and Děčín, and the results showed that the EFs of both cities were at comparable or even higher levels than the average values for the whole Czech Republic. The peri-urban area showed surprisingly high values for all EFs and habitat connectivity. The urban–rural gradient of EFs also showed higher values for EFs in the peri-urban area than in the adjacent rural (forest and agricultural) landscape. The method can serve as a useful tool to quickly identify valuable urban habitats (strong ESs providers) to support their protection or to identify places with low functional values that should be considered and sorted in urban adaptation strategies to global climate change to support the creation of functional green infrastructure.